Role of platelet indices and vitamin D in forecasting deterioration of glycemic control and vascular complications in type 2 diabetes - Maryam Ahmed Obaid Al Ali; Khalid Abdelsamea Mohamedahmed; Asaad Ma Babker (Italian Journal of Medicine)
Type 2 diabetes mellitus (T2DM) is a prevalent chronic condition associated with various complications, including vascular ones. Platelet indices and vitamin D have been proposed as potential predictors of glycemic control deterioration and vascular complications in T2DM patients. This study aimed to investigate the predictive role of platelet indices and vitamin D in the development of vascular complications and deterioration of glycemic control in type 2 diabetic patients attending Thumbay Hospital, Ajman. In this cross-sectional study, data were collected from individuals divided into two groups: a controlled group and a patient group with T2DM from the Thumbay Hospital and Thumbay Laboratory. A total of 100 individuals aged between 20 and 75 years was included. Demographic information, vitamin D levels, and platelet indices were collected and analyzed using appropriate statistical tests. The demographic distribution of T2DM patients revealed that males accounted for 56.76% of the sample, while females represented 43.22%. The analysis of vitamin D levels showed that 58% had a deficiency, 23% had an insufficiency, and 19% fell within the optimal range. Platelet indices were evaluated in relation to glycemic control, and significant associations were found between vitamin D levels and mean platelet volume (MPV) as well as platelet distribution width (PDW). Post-hoc tests indicated significant differences in plateletcrit values among specific glycemic control groups. Furthermore, diabetic patients had significantly higher levels of fasting blood glucose and hemoglobin A1C compared to the control group, along with higher MPV and slightly lower PDW. The findings suggest a potential predictive role of platelet indices and vitamin D in the deterioration of glycemic control and the development of vascular complications in T2DM patients attending Thumbay Hospital, Ajman.